মুজিব ভাই - মুসা, এ বি এম (ঢাকা : প্রথমা প্রকাশন, 2012)
Articles on the life and work of Sheikh Mujibur Rahman, 1920-1975, politician and former president of Bangladesh.
In Bengali.
Keywords: Mujibur Rahman, -- Sheikh, -- 1920-1975.; Politicians -- Bangladesh -- Biography; Ex-presidents -- Bangladesh -- Biography; Bangladesh -- Politics and government -- 1971-